Aspects of architecture infrastructures acculturation function, form and the meaning of the Christian Church building Pniel Blimbingsari in Bali - Stephanie Arvina Yusuf (ARTEKS : Jurnal Teknik Arsitektur, 2016)
When culture and Christianity entered Blimbingsari Village, Bali was the beginning of combination between local and migrant culture. Combination of both cultures became an acculturation in architectural form. It is materialized in architecture of Gereja Kristen Pniel Blimbingsari, Bali. Church building form was no longer as an idea generally with the characteristics soaring roof, Gothic architecture style, and so on. Preliminary studies indicate that Gereja Kristen Pniel Blimbingsari through the acculturation process that affect in architectural form and religious rituals. This study aims to reveal a form of acculturation occurs seen from the aspect of function, form and meaning of the building. The method in this research that is descriptive, analytical, and interpretative based on field studies and empirical evidence. This approach taken grounded in cultural theory and archetypes in architecture which collaborated with the aspect of function, form, and meaning of architecture. The study concluded that occur relations between function, form and meaning that implies domination in the form of architecture acculturated. The study concludes that there was a relation between function, form and meaning which implies the dominance in the form of architecture that acculturated. Dominance in this study is as a result of interpretation from the analysis conducted. The concept of Asta Kosala Kosali have a dominant role in shaping the architectural form of acculturation Gereja Kristen Pniel Blimbingsari. The study is expected to benefit as a reference to a similar case that acculturation and can contribute knowledge in the realm of architecture.